Management Ownership, Audit Committee, Independent Commissioner, And Company Size Affect the Integrity of Financial Statements - Menik Indrati; Gilang Andhika Marsa (Budapest International Research and Critics University, 2022)
The purpose of this study is to analyze the effect of managerial ownership, audit committee, independent commissioner, and firm size on integrity of financial statement. This study consists of four independent variables consisting of managerial ownership is proxied by the proportion of share ownership by management, the audit committee is proxied by the number of audit committee meetings, independent commissioners are proxied by the proportion of independent commissioners, and company size is proxied by LN total assets, and one variable dependent namely the integrity of financial statements proxied by earnings management. In this study, there were 84 companies that met the research criteria with the object of research being non-financial industrial sector companies listed on the Indonesia Stock Exchange (IDX) during the period 2019-2020. The results indicate that managerial ownership, audit committees, independent commissioners, and firm size has simultaneous effect on earnings management. The managerial ownership variable has negative effect on earnings management. The audit committee has no effect on earnings management. Independent commissioners have negative effect on earnings management. Firm size has no effect on earnings management. This research can also be an evaluation material for companies and investors and provide additional information about what factors affect earnings management.